2010
DOI: 10.1002/btpr.524
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth temperature on the production of antibody Fab fragments in different microbes: A host comparative analysis

Abstract: Microorganisms encounter diverse stress conditions in their native habitats but also during fermentation processes, which have an impact on industrial process performance. These environmental stresses and the physiological reactions they trigger, including changes in the protein folding/secretion machinery, are highly interrelated. Thus, the investigation of environmental factors, which influence protein expression and secretion is still of great importance. Among all the possible stresses, temperature appears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 54 publications
3
20
1
3
Order By: Relevance
“…This has directly affected the production of heterologous proteins that requires maintaining a constant specific growth rate. Our results shown a higher concentration when the yeast was grown at 10 °C, differing from those observed at 15 °C in such yeasts as P. pastoris and Saccharomyces cerevisiae , where the biomass was reduced (Steels et al , 1994; Pizarro et al , 2008) and where methanol could have negative effects on cell growth compared to other inductors such as glycerol and glucose (Dragosits et al , 2011). …”
Section: Discussioncontrasting
confidence: 86%
“…This has directly affected the production of heterologous proteins that requires maintaining a constant specific growth rate. Our results shown a higher concentration when the yeast was grown at 10 °C, differing from those observed at 15 °C in such yeasts as P. pastoris and Saccharomyces cerevisiae , where the biomass was reduced (Steels et al , 1994; Pizarro et al , 2008) and where methanol could have negative effects on cell growth compared to other inductors such as glycerol and glucose (Dragosits et al , 2011). …”
Section: Discussioncontrasting
confidence: 86%
“…In this context, environmental conditions have a significant impact on the levels of recombinant proteins. For instance, lower culture temperature [12, 13], low oxygen availability [14], as well as adequate substrate feeding strategies in high cell density cultures [15, 16], and type of carbon source(s) [17, 18] resulted in positive effects on protein secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen availability can effect growth rates and energy availability (7), which may alter plasmid replication or partitioning. Studies have also shown that reducing growth temperatures can improve yields if toxicity is suspected (8), but it can also be detrimental to the expression of IMPs (1) ( see Note 58 ). Several reports have shown chemical chaperones can increase protein expression levels by improving the folding of IMPs (9,10).…”
Section: Methodsmentioning
confidence: 99%